WACANA PEMBUNGKAMAN TERHADAP PEREMPUAN SEBAGAI KORBAN KEKERASAN SEKSUAL DALAM FILM PENYALIN CAHAYA (2021) - Octari Ambarita, Angelica; Sunarto, Sunarto; Ratri Rahmiaji, Lintang (Interaksi Online, 2024)
Reports regarding cases of sexual violence were still very high throughout 2022 with the majority of victims being women. Law enforcers always settled on the ‘peaceful’ way of resolving cases by not taking sides with victims or being unjust. Film was a discourse that represents social realities. Based on the social issues, Photocopier was produced to depict the silencing that still occurred against victims of sexual violence. The research aimed to examine the discourse on silencing women as victims of sexual violence which was portrayed in Photocopier. Muted Group Theory by Cheris Kramarae was used as the main theory, followed by the concept of radical-libertarian feminism. Sara Mills’ Critical Discourse Analysis was used as the research method to analyze deeper on four aspects of examination: character, fragmentation, focalization, and schemata. The results indicated that the female characters in Photocopier represent women as victims of sexual violence. Despite having important roles, the female characters were still portrayed to be silenced by the male characters. Fragmentation concentrated on the facial expressions of the characters which depicted anger and frustration of the victims. Focalization in the film indicated that the female victims were active subjects. The subjectivity of sexual violence victims rendered through feminine-oriented when sharing their experiences. Hence, schemata identified the victim blaming ideology in which the female victims of sexual violence still struggle to reveal the truth and demand lawfulness.